Transformasi Supervisi Kepala Sekolah di Era Digital: Tinjauan Sistematis terhadap Model dan Pendekatan Terbaru - Resdayani Resdayani (Journal of Innovation in Teaching and Instructional Media, 2025)
The digital era has brought significant changes in various aspects of education, including school principals' supervision. This study aims to systematically review the latest models and approaches in school principal supervision in the digital era. Using a systematic literature review method, this research identifies key trends in supervisory transformation, including the utilization of digital technology, strengthening instructional leadership roles, and data-driven collaborative strategies. The findings indicate that digital supervision enhances effectiveness through the use of online platforms, real-time data analysis, and increased teacher engagement in professional development. This study provides implications for policymakers and education practitioners in designing adaptive supervisory policies aligned with technological advancements.